Upaya Meningkatkan Minat dan Hasil Belajar Matematika menggunakan Media Juku Kelas II di Sekolah Dasar - Fajarani, Hanifan; Choiriah Widyasari; Esti Nur Qorimah (Jurnal Penelitian Pendidikan, 2024)
This research aims to increase interest and learning outcomes in mathematics using "JUKU" media. This type of research is Classroom Action Research (PTK), which is carried out through four stages, namely planning, action, observation, and evaluation/reflection. The subjects of this research were class IIB students at SD Muhammadiyah 23 Surakarta, with a total of 28 students. This research data was obtained through observation and written tests given by researchers through evaluation questions. The research results obtained were that students' interest and learning outcomes in mathematics on addition and subtraction material increased. In cycle I, the average result of students' interest in learning mathematics was 68.74% and in cycle II students had experienced an increase with a percentage of 87.71%. Apart from that, students' mathematics learning outcomes also increased. The average percentage of learning outcomes in cycle I was 69.39% and the percentage of completeness was 60.71%. Then in cycle II there was an increase in the average learning outcomes by 88.67% and the percentage of learning completion also increased by 85.71. So it can be concluded that there has been an increase in students' interest and learning outcomes in mathematics after being given treatment using the "JUKU" media.